An eloquent and persuasive Mr. Smee - Erio Tosatti (JCOM: Journal of Science Communication, 2006)
John Ziman with his old-fashioned ways, was a real British gentleman of the colonies. Born and raised in New Zealand, Ziman belonged to that large group of men and women that went back to their fathers’ land in the last century from the Commonwealth countries. In many cases, they were individuals with an outstanding intellect and, therefore, a real tresure trove for Great Britain, which drew from those remote places not only gems, tea, perfumes and raw materials, but also enlightened minds and reliable personalities.